Secret Affairs Franklin Roosevelt, Cordell Hull, and Sumner Welles - Gellman, Irwin (Johns Hopkins University Press, 2019)
Originally published in 1995. President Franklin Delano Roosevelt was paralyzed from the waist down, but he concealed the extent of his disability from a public that was never permitted to see him in a wheelchair. FDR's Secretary of State was old and frail, debilitated by a highly contagious and usually fatal disease that was as closely guarded a state secret as his wife's Jewish ancestry. The undersecretary was a pompous and aloof man who married three times but, when intoxicated, preferred sex with railroad porters, shoeshine boys, and cabdrivers. These three legendary figures-Franklin Roosevelt, Cordell Hull, and Sumner Welles-not only concealed such secrets for more than a decade but did so while directing United States foreign policy during some of the most perilous events in the nation's history. Irwin Gellman brings to light startling new information about the intrigues, deceptions, and behind-the-scenes power struggles that influenced America's role in World War II and left their mark on world events, for good or ill, in the half-century that followed. Gellman had unprecedented access to previously unavailable documents, including Hull's confidential medical records, unpublished manuscripts of Drew Pearson and R. Walton Moore, and Sumner Welles's FBI file. Gellman concludes that while Roosevelt, Hull, and Welles usually agreed on foreign policy matters, the events that molded each man's character remained a mystery to the others. Their failure to cope with their secret affairs-to subordinate their personal concerns to the higher good of the nation-eventually destroyed much of what they hoped would be their legacy. Roosevelt never explained his objectives to his vice president, Harry Truman, or to anyone else. Hull never groomed a successor, and Welles kept his foreign assignations as classified as his sexual orientation. Gellman tells the dramatic story of how three Americans-despite private demons and bitter animosities-could work together to lead their nation to victory against fascism.